Pengaruh Keterlambatan Dokumen Kapal Bermuatan Batubara pada PT. Pelayaran Bahtera Adhiguna Cabang Panjang - Yusuf Sungguh Raja Sihombing; Syarifur Ridho; Aja Avriana Said (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
As a shipping company that operates in the agency sector and handles its own routine ships in transporting coal, PT. The Long Branch Adhiguna Ark Shipping also handles ship documents. A ship is declared seaworthy or can sail to carry and unload goods if it is equipped with ship documents that have been approved by the harbormaster. The harbormaster only asks for these documents specifically for local ships. Almost every ship document that is being loaded at the special terminal of PT. Bukit Asam, which is served by an agency company, experienced document deays. The result of deays in this document can affect the ship's activities/activities at the port. One of them is that the ship is removed first from the special port of PT. Bukit Asam (Persero) because it has exceeded the specified waiting time limit. So the ship will return to anchorage, waiting for the exit document process to be completed. The length of time the document process was completed hampered the ship's departure to fulfill its trip (voyage), thereby reducing coal deiveries for the PLTU's needs and this gave rise to complaints from the PLTU. One solution is for the agent to frequently coordinate with reated parties for the smooth running of activities.